Information and communications technologies and IFPRI's mandate: a conceptual framework - Chowdhury, Nuimuddin (International Food Policy Research Institute, 2000)
A cluster of information and communications technologies (ICTs) has not only pervasively penetrated the world of communications and entertainment, but also affected the way we earn and spend, heal and learn, save and search, and share information, both important and banal. In some countries it has brought changes to the universe of policymaking and governance. These technologies process various kinds of information (voice, video, audio, text, data) and also facilitate various forms of communication among human agents, between human agents and information systems, and among information systems. By pronouncing the death of distance, these technologies have fundamentally changed the techno-economic paradigm of production and distribution, especially of services.The demand for skills in any of these ICTs has dramatically increased. Competence in them, which often though not always requires extensive formal education, has paid well for those who possess the requisite skills. Some skeptics, however, still do not see any role for ICTs in efforts to alleviate poverty and bring food security to rural and urban areas of developing countries. But realists respond that in the increasingly global village that the world is fast becoming, ICTs are rapidly changing the standards for the economic person. And ICTs have the potential to help the poor to acquire literacy or marketable skills. Employment and growth are at stake: a modern, high-speed information infrastructure is critical in determining where large international companies will locate. ICTs have the potential to improve the access of the poor to information anytime, anywhere, and thus to increase their productivity.